Pelleting tidak Menghambat Perkecambahan Benih Padi Sawah (Oriza sativa L.) - Pranata, Cahya Adi; Agustiansyah, Agustiansyah; Timotiwu, Paul Benyamin; Pramono, Eko (JURNAL AGROTROPIKA, 2022)
The stages of seeding paddy rice seeds before planting require more time, cost, and labor than seeds that are planted directly without the seeding stage. Pelleting is an alternative technology in planting small-sized rice seeds without going through the seeding stage. This study aims to determine the effect of pelleting on the germination of paddy rice seeds. This experiment is a non-factorial experiment consisting of 9 treatments and repeated 3 times in a Randomized Block Design (RBD). The nine treatments were: (P0) No pellets, (P1) Clay + CMC + Dolomite 4 g, (P2) Clay + CMC + Dolomite 12 g, (P3) Clay + AG + Chalk 4 g, (P4) Clay + AG + Chalk 12 g, (P5) Clay + CMC + Mycorrhizae, (P6) Clay + AG + Mycorrhizae, (P7) Clay + CMC + Trichoderma, (P8) Clay + AG + Trichoderma. The data obtained were analyzed for variance and performed with the Honest Significant Difference (HSD)test using the R-studio statistical program. The results showed that the pelleting technique did not inhibit rice seed germination as indicated by the variables of germination, time of emergence of plumules, speed of germination, vigor index, normal germination root length, normal germination colept length, normal germination wet weight, normal germination dry weight. This means that clay can be used as a filler, Carboxyl methyl cellulose (CMC) and Arabic gum (AG) as an adhesive and microorganisms (mycorrhizae and trichoderma) can be added as seed pellet material